Perilaku Seksual Pranikah Berisiko pada Mahasiswa yang Menyebabkan Kehamilan Tidak Diinginkan (KTD) - Muhammad Azinar; Zahroh Shaluhiyah; Harbandinah Pietojo (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
Premarital sexual behavior in the students is rising up. The cases of unwanted pregnancy, abortion, and premarital sexual infection increasingly occur in the students. This study was one of explanatory research using Cross-sectional approach. The sample of this research was some university students of adolescence (18-24 year of age) from six colleges in Semarang municipality of 382 students. The sample was taken using proportional simple random sampling.: This research showed that 17,2% of male students and 6,5% of female students have a premarital sexual behavior that risk unwanted pregnancy. The bivariate analysis result using chi square test indicated that there were five variables significantly correlated to university students’ premarital sexual behavior, namely religiosity, attitude, access and contact to information media, comrades’ attitude and comrades’ sexual behavior. From the logistic regression test result, the dominantvariables influencing unwanted pregnancy risk premarital sexual behavior of male students in university were comrades’ sexual behavior and religiosity. While of female students were comrades’ sexual behavior.